A Study on the Promotion Effectiveness of Recommender System - Wang, Chuan Yu (2019)
This research aims to examine the relationship between perceived trust and promotion effectiveness of recommendation system. Specifically, this research explores the relationship between three types of trusts namely, competence trust, benevolence trust and integrity trust and perceived Recommendation Agent (RA) trust.